(3TQM (B" (3ZQGei UMjM (B" (3aj eUWdM GdMOjKs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg eMeO Hf YHO Gddg hHYO ajbhd GdYHO GdabjQ Edi QMeg QHg GdYah GdbOjQ eMeO GdSYjO Hf eMi GdOjf cGf Gddg dg hdCMHJg Cejf Ef GdCHjGJ GdeJVefI CdbGH GdMOjK dZRkG hGdeTjQI EdjgG s
(3BNQgG (B:s
(3hcJH ebjOkG dPdc eMeO GdSYjO Hf eMi GdOjf (B_ (3hfMf CSQi HCjOi GdaQGfSjS (B_ (3YGe (B1266 (3bdJ hbO ESJLGH Gddg OYGAfG afMf GdBf HOeTb GdTGe ai CQZO YjT hCWjH hddg GdMeO hGdefI HChGFd QeVGf (B1275 s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdMOjK h GdeUWdMs